Can Electrical Resistance Tomography be Used to Monitor the Distribution of Moisture in Cement-Based Materials?. (May 2019) - Jiang, Yong; Qin, Lei; Ren, Hongwei
Abstract: It is important to develop a tool to monitor moisture distribution in cement-based materials, because freeze-thaw of concrete, corrosion of steel bars, carbonization and other problems occur in the presence of water. In this paper, the feasibility of monitoring water distribution in cement-based materials by electrical resistance imaging (ERT) is studied. In ERT technology, the resistivity distribution is reconstructed by detecting the voltage at the boundary of the test block, and the structure and state of the object are presented by the image. The experimental results show that ERT technology can monitor the moisture distribution and outline in cement-based materials.